Implementation of the Least Significant Bit Method for Hiding Text in Digital Images - Harmoko Lubis; Jontinus Manullang (Jurnal ICT : Information and Communication Technologies, 2023)
To speed up the process of sending secret messages, we need a medium for small messages that can still guarantee the confidentiality of the messages they contain. GIF (Graphics Interchange Format) is an image format that is one of the most commonly used formats on the web because of its small size and for encrypting the text that is sent. Encryption is carried out at the time of delivery by converting the original data into confidential data, while decryption is carried out at the time of receipt by converting the confidential data into original data. The most common way to hide messages is to use the Least Significant Bit (LSB). This research has succeeded in implementing the LSB algorithm to solve steganography on digital images in GIF format optimally